(untitled) (Research, Society and Development, 2023)
Objective: To identify the microbiological profile of infections in elderly patients affected by SSI at a University Hospital in the Northeast. Methodology: This is a descriptive, exploratory, cross-sectional study, in which the advantages are that it allows researchers to directly observe the phenomenon under study in elderly patients over 60 years of age, gathering information in a short period between January 2022 and July 2023 and is approved by the Research Ethics Committee of the University Hospital of the Federal University of Piauí, CAAE No. 46437921.3.0000.8050. Results: There was a significant difference in involvement between females and males, with a greater number of female patients. Regarding specialty, Orthopedics and Traumatology (n = 14; 29.16%), General Surgery (n = 8; 16.66%) and Cardiology (n = 7; 14.58%) were surgical specialties that obtained a higher ISC number. Discussion: Regarding the distribution of surgeries according to their anatomical plans, there was a higher frequency in Organ/Cavity (n = 10; 20.83%) and superficial (n = 9; 18.75%). Another factor in the study was the isolated microorganism, Escherichia coli (n = 4; 21.05%) and Klebsiella pneumoniae (n = 3; 15.79%), both gram-negative bacteria. Conclusion: The present study, through the data shown here, reinforces the need to carry out actions aimed at preventing SSI, since it is extremely important to strengthen SSI prevention protocols.